Menandingi Reduksionisme Ekologis: Menceritakan Hubungan Ekologis Menyakitkan dalam Etnografi Komunitas Rural - Riyanto, Geger (MAARIF Institute, 2024)
Based on a personal reflection of ethnographic fieldwork, this paper presents strategies for depicting the relationship between rural communities and their landscapes. The relationship between rural communities and their environment is frequently portrayed as harmonious and non-exploitative. However, this portrayal oversimplifies the more complex socio-ecological dynamics. Ecological adaptation ethnographies, which capture the individual relationship with nature, are prone to be interpreted as exemplifications of local wisdom, justifying this reductionism. An ethnographic moment that should be highlighted is rural communities’ painful experience with their landscapes. These moments vividly demonstrate how humans are constantly confronted with uncertainty in their interactions with their environment and the ever-changing dynamics between them. My exposure to the painful experiences of local residents in their ecological relationships, which I will discuss here, compels me to turn away from frameworks that oversimplify the relationship between the two.